1988
DOI: 10.1002/hep.1840080637
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytic lipoprotein receptors and intracellular lipoprotein catabolism

Abstract: Hepatocytes, as the major site of synthesis and terminal catabolism of plasma lipoproteins, exert the major regulatory influence on the concentration of atherogenic lipoproteins in blood plasma and may thereby influence the rate of atherogenesis. The LDL receptor on the microvillous sinusoidal surface of hepatocytes mediates the catabolism of remnants of triglyceride-rich lipoproteins and LDL. Binding of VLDL remnants to the receptor, mediated by apo E, is of very high affinity and presumably multivalent, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 138 publications
3
47
0
1
Order By: Relevance
“…Alternatively, the process of LDLR internalization may differ in hepatocytes and fibroblasts. For example, most LDLRs are clustered in coated pits in fibroblasts but appear to be dispersed on the plasma membrane in hepatocytes (31,32). ARH may perform a specific function in hepatocytes that is not required in fibroblasts.…”
Section: Fig 8 Mapping Of the ␤2-adaptin Binding Site In Arhmentioning
confidence: 99%
“…Alternatively, the process of LDLR internalization may differ in hepatocytes and fibroblasts. For example, most LDLRs are clustered in coated pits in fibroblasts but appear to be dispersed on the plasma membrane in hepatocytes (31,32). ARH may perform a specific function in hepatocytes that is not required in fibroblasts.…”
Section: Fig 8 Mapping Of the ␤2-adaptin Binding Site In Arhmentioning
confidence: 99%
“…30,31 This subcellular fractionation procedure distinguishes 3 endosomal fractions on the basis of their morphology and their association with, or the absence of, various radioligands at different time points: ''early'' (compartment of uncoupling receptors and ligands [CURL]) and ''late'' (multivesicular bodies [MVB]) endosomes and a third endosomal fraction, the receptor-recycling compartment (RRC), which is enriched in recycling receptors and depleted of ligands. 27,32 Although biochemical analyses have shown a very similar protein composition, 28 the electron microscopy study of the isolated endosomes showed ultrastructural differences between the fractions 27,29,31,33 (Fig. 1).…”
mentioning
confidence: 90%
“…This seemed to be due to the VLDL-(or chylomicron-) like lipoprotein triggering an efflux of intracellular lipids. In mammalian cultured cells such as small intestinal crypt cells (3,4) and fibroblasts (5), HDL is resecreted with intracellular cholesterol following endocytosis after binding of HDLto the cells (3,4,8,26,27,29), or HDL withintracellular cholesterol is released from the specific binding proteins of plasma membraneof the cells following cellular signal induction such as the activation of phospholipase D and protein kinase C (4-7, 24). In these cells HDLis the only lipoprotein to participate in the efflux of cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics of the effects of HDLdescribed above suggest the novel role of HDLin the transport of lipids. Though there are two hypotheses on the role of HDLfor cholesterol efflux, namely HDL-retroendocytosis (3,4,8,26,27,29) and cellular signal transducing by HDL(4-7, 24), neither hypotheses seems to be applicable to the role of eel serum HDL,since HDLin eel hepatocytes seems only to provide the initial step for the transport of lipids and HDLitself seems not to participate in transporting intracellular lipids. Instead, a VLDL-(or chylomicron-) like lipoprotein transports the intracellular lipids in eel hepatocytes.…”
Section: Resultsmentioning
confidence: 99%